Community participation in tourism microenterprises among Amanah Ikhtiar Malaysia borrowers in Semporna, Malaysia - Ibrahim, Mohd Romzee; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (Universiti Malaysia Sarawak, 2018)
Tourism industry is seen as a sector that could possibly provide opportunities to the local community by the creation of tourism enterprises. These tourism enterprises are in most likely situations to be micro businesses established and operated by the local community. This paper highlights lack of participation in tourism microenterprises among local community, these self-employed local community run their business as a need for survival and without formal education and entrepreneurial skills. A structured face to face survey was administered to evaluate local community participation in tourism related micro enterprises among Amanah Ikhtiar Malaysia (AIM) borrowers in Semporna, Sabah. The selected borrowers were identified through a multi-stage random sampling methods. Analysis of association and relationship among the socio demographic and enterprises characteristics using chi-square test of independence revealed that their level of participation is associated with level of education, location, number of employees, gross income, capital, assets and loan frequency. The microfinance institution is recommended to incorporate appropriate entrepreneurial skills to suit local environments in tourism and integration with various stakeholders such as local authorities at federal and state government, tourism agencies and non-governmental agencies is essential in its delivery system to facilitate the creation of sustainable entrepreneurship activities especially towards tourism microenterprises.